A WORD IS WORTH A THOUSAND IMAGES. THE IMPORTANCE OF RECOVERING LINGUISTIC REFLECTION IN HIGH SCHOOL CLASSROOMS - Angélica Vaninetti (Universidad Nacional del Nordeste, 2019)
In this article, we will present an auric experience carried out with 5th graders. year of a high school, located in Greater Buenos Aires, related to the comprehensive and critical reading of a representative novel of Naturalism in Argentina. Students manifest serious difficulties in making a reading that means inferring ideas from implicit content or understanding the meaning of explicit expressions, figuratively or literally. For this reason, we propose a work perspective that tries to revitalize the study of the word, from a lexical-syntactic and semantic approach, since we consider that this knowledge is an essential tool to guide the path towards connotative reading. We know that interpreting a text implies discovering the key words and nuclear sentences that contain relevant information. Undoubtedly, this requires knowing the various grammar resources that guide the reader so that he can make pertinent deductions. However, the reflexive study of these resources, including that of the word and its characterizations, is usually considered an isolated discipline, as if the lexical-syntactic composition of a text does not guide the activity carried out by the reader. For this reason, our interest is in inducing students towards a committed reflection on the use of the different kinds of words and the possible combinations in which they participate, so that the transfer of this knowledge promotes the formation of Critical readers of literary and / or academic texts.